A multi-mineral intervention to counter pro-inflammatory activity and to improve the barrier in human colon organoids - Varani, James; McClintock, Shannon D.; Nadeem, Daniyal M.; Harber, Isabelle; Zeidan, Dania; Aslam, Muhammad N. (Frontiers in Cell and Developmental Biology, 2023)
Ulcerative colitis is a chronic inflammatory condition, and continuous inflammatory stimulus may lead to barrier dysfunction. The goal of this study was to assess barrier proteomic expression by a red algae-derived multi-mineral intervention in the absence or presence of pro-inflammatory insult. For this purpose, human colon organoids were maintained in a control culture medium alone or exposed to lipopolysaccharide with a combination of three pro-inflammatory cytokines (tumor necrosis factor-α, interleukin-1β and interferon-γ [LPS-cytokines]) to mimic the environment in the inflamed colon. Untreated organoids and those exposed to LPS-cytokines were concomitantly treated for 14 days with a multi-mineral product (Aquamin®) that has previously been shown to improve barrier structure/function. The colon organoids were subjected to proteomic analysis to obtain a broad view of the protein changes induced by the two interventions alone and in combination. In parallel, confocal fluorescence microscopy, tissue cohesion and trans-epithelial electrical resistance (TEER) measurements were used to assess barrier structure/function. The LPS-cytokines altered the expression of multiple proteins that influence innate immunity and promote inflammation. Most of these were significantly decreased with Aquamin® alone but only a modest decrease in a subset of these proteins was detected by Aquamin® in the presence of LPS-cytokines. However, a subset of inflammation-related proteins including fibrinogen-β and -γ chains (FGB and FGG), phospholipase A2 (PLA2G2A) and SPARC was significantly down-regulated in the presence of Aquamin® (alone and in combination with LPS-cytokines); another subset of proteins with anti-inflammatory, antioxidant or anti-microbial activity was up-regulated by Aquamin® treatment. When provided alone, Aquamin® strongly up-regulated proteins that contribute to barrier formation and tissue strength. Concomitant treatment with LPS-cytokines did not inhibit barrier formation in response to Aquamin®. Confocal microscopy also displayed increased expression of desmoglein-2 (DSG2) and cadherin-17 (CDH17) with Aquamin®, either alone or in the presence of the pro-inflammatory stimulus. Increased cohesion and TEER with Aquamin® (alone or in the presence of LPS-cytokines) indicates improved barrier function. Taken together, these findings suggest that multi-mineral intervention (Aquamin®) may provide a novel approach to combating inflammation in the colon by improving barrier structure/function as well as by directly altering the expression of pro-inflammatory proteins.